The Effectiveness of Measuring Thiopurine Metabolites in the Treatment of Autoimmune Hepatitis Patients - Yassin, Woroud; Nasser, Roni; Veitsman, Ella; Saadi, Tarek (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The thiopurine drugs-azathioprine and mercaptopurine-are purine antimetabolites used for the treatment of autoimmune hepatitis. These drugs undergo metabolism through genetically determined pathways, which influences their effectiveness and toxicity. There is scarce information regarding the clinical effects of measuring drug metabolites in these patients. The goal of the study is to test the clinical significance of measuring thiopurine metabolites in patients unsuccessfully treated with thiopurines. Materials and Methods: Clinical and laboratory data collected for patients who were treated for autoimmune hepatitis between 2015 and 2018, and did not achieve full remission under thiopurine therapy and had thiopurine metabolite levels measured due to lack of response and suspicious side effects were chosen. We compared clinical and laboratory data before and after the therapy change. Results: The study included 25 tests of thiopurine metabolites in 21 patients. Six tests had therapeutic levels. Three tests showed high levels leading to lowering the drug dose. In 11 cases, levels of 6-thioguanine nucleotide were low; the dose was not changed in 3 of these, and the dose was increased in the remaining 8. Shunting was observed in 5 cases, 2 of which were mild and the dose was not changed. In the remaining 3, the dose was decreased, and allopurinol was added. Significant improvements in liver enzymes were observed following dose adjustments. Conclusion: We showed that, in cases of suboptimal response to thiopurine treatment, measuring thiopurine metabolites had an important role in optimizing therapy. In most patients, changing the dose led to a significant improvement with no need to switch to secondline therapies. Cite this article as: Yassin W, Nasser R, Veitsman E, Saadi T. The effectiveness of measuring thiopurine metabolites in the treatment of autoimmune hepatitis patients. Turk J Gastroenterol. 2024;35(3):232-238.